Truth and Justice in the polarized political scene: recent debates on the legitimacy of trials for crimes against humanity (Argentina, 2015) - Quaretti, Lucia (Revista de Historia Social y de las Mentalidades, 2026)
This article examines the debate on the articulation between truth and justice and the legitimacy of trials for crimes against humanity in Argentina around 2015, in a context of increasing political polarization. In this setting, the singularity of the interventions was often reduced to the notions of “impunity” and “revenge.” However, through a qualitative analysis of public documents, four positions are identified: the rejection of retribution, the proposal to reduce sentences in exchange for information, the denunciation of the pursuit of impunity, and the defence of trials as a means of achieving truth. Thus, the articulation between truth and justice remains an open question that cannot be closed.